Educação financeira: uma revisão sistemática da literatura - SANTOS, Debora Correa dos (2023)
The present study presents the importance of working with financial education and especially with financial indexes in the school environment. The general objective is to map the discussions on financial education in accounting sciences from 2018 to 2022 in the repositories of the Federal University of Rio de Janeiro - UFRJ and Federal University of Pará - UFPA. The theoretical framework has the support of (SILVA, 2016), (BARRETO, 2019; COELHO, 2016), (AZEREDO; URIAS; CABRAL, 2018). In the Methodological field, the systematic review technique was used to carry out the descriptive research, which had a primarily qualitative approach. 10 articles are included in the systematic evaluation of the literature after applying the exclusion criteria of direct and clear language, five from each institution analyzed. Ultimately, financial education stems from the knowledge that it is essential for people to become more aware of the opportunities and risks associated with each circumstance, in the sense that they can have a fuller financial education and, consequently, better allocate their financial resources. in order to provide a better quality of life for you. The proposal for a study of this nature contributes to the academic community and the mapping of national scientific production, which can serve as a guide for anyone looking for research material for studies on financial education.